PERBEDAAN MOTIVASI BELAJAR ANTARA ANAK KORBAN PERCERAIAN DAN ANAK DARI KELUARGA UTUH - Nurussakinah Daulay; Sri Hariati Hrp; Kamila Soraya; Tiara Afrillia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to find out the comparison, especially the learning motivation of students in families who experienced divorce (broken homes) with intact (harmonious) families, in addition to knowing the teacher's strategy in dealing with students with broken homes at the school. The source of the data obtained in this study was that there were 254 students at Al Ulum Tuasan Islamic High School, Medan. Data collection techniques in this study used a research instrument by giving a questionnaire. The research method used is quantitative description. The focus of the research is the problem of learning motivation of children who experience broken homes. The results of this study indicate that children who have incomplete families (absent father or mother or both), lack high learning motivation. In addition, the strategies carried out by teachers at Al Ulum Tuasan Islamic High School, Medan show that teachers teach with a variety of learning strategies and methods such as lecture, discussion, question and answer methods, and assignments so that students are motivated to take part in learning and are active and affective so that students are not bored and bored in the learning process takes place.